A Model of Transformative Religious Education: Teaching and Learning Islam in Pondok Modern Darussalam Gontor, Indonesia - Jusubaidi, Jusubaidi; Lindgren, Tomas; Mujahidin, Anwar; Rofiq, Ahmad Choirul (Millah: Journal of Religious Studies, 2024)
This research aims to examine character education in pesantrens (Islamic boarding schools also known as pondok pesantren) as a model of religious education in transforming the attitudes of students in line with the values and culture of a diverse society. This study is based on documents related to the curriculum and student guidance system, which were confirmed through interviews with leaders and teachers, as well as observations at Pondok Modern Darussalam Gontor, Indonesia. The research findings indicate that Pondok Modern Darussalam Gontor, Indonesia, has implemented a transformative education system. Students have undergone a transformation from traditional, fanatic, and closed values to modern, rational, disciplined, inclusive, independent, and responsible ones. The transformation in students' personalities occurs not only through classroom learning but also through reflective engagement in pesantren management, discussions, and public speaking exercises. The findings of this study imply that the religious education system in pesantrens should prioritize not only the cognitive aspects of doctrinal religious knowledge, but also involve students in society, fostering open, tolerant, and rational characters.